Penentuan Seleksi Kejuaraan Karate Shoto-Kai Dengan Metode Welch Powell - Kevin Gideon Simanjuntak; Nenna Irsa Syahputri; Dharmawati (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
The world of martial arts is very well known in various national and international regions. There are several that show martial arts, one of which is Karate. Karate is a martial art that is applied in a national level sports branch in Indonesia. Karate has 3 training branches, namely Shoto-Kai, Inkanas and Lemkari. A martial art will always select the schedule for each event held by the committee, one of which is Shoto-Kai karate. The aim of this research is to build a selection system for various categories using the Welch Powell method which previously was still done manually, therefore the selection can be automatically inputted by participant data into an application. This application uses Microsoft Visual Basic, making it easier for the committee to determine participants in selecting the karate competition schedule. Based on the test results, the application obtained can run successfully so that it can use a laptop/computer. This research can be a medium of information regarding karate selection and can provide smoothness to achieve success.